Immunogenetics of longevity and its association with human endogenous retrovirus K - James, Lisa M.; Georgopoulos, Apostolos P. (Frontiers in Aging, 2025)
IntroductionThe human immune system is equipped to neutralize and eliminate viruses and other foreign antigens via binding of human leukocyte antigen (HLA) molecules with foreign antigen epitopes and presenting them to T cells. HLA is highly polymorphic, resulting in subtle differences in the binding groove that influence foreign antigen binding and elimination. Here we tested the hypothesis that certain HLA alleles may promote longevity by enhanced ability to counter virus antigens that may otherwise contribute to morbidity and mortality.MethodsWe utilized high-resolution genotyping to characterize HLA and apolipoprotein E in a large sample (N = 986) of participants (469 men, 517 women) ranging in age from 24 to 90+ years old (mean age: 58.10 years) and identified 244 HLA alleles that occurred in the sample. Since each individual carries 12 classical HLA alleles (6 alleles of each Class I and Class II), we determined in silico the median predicted binding affinity for each individual (across the 12 HLA alleles) and each of 13 common viruses (Human Herpes Virus 1 [HHV1], HHV2, HHV3, HHV4, HHV5, HHV6A, HHV6B, HHV7, HHV8, human papilloma virus [HPV], human polyoma virus [JCV], human endogenous retrovirus K [HERVK], and HERVW). Next, we performed a stepwise multiple linear regression where the age of the participant was the dependent variable and the 13 median predicted HLA-virus binding affinities were the independent variables.ResultsThe analyses yielded only one statistically significant effect–namely, a positive association between age and HERVK (P = 0.005). Furthermore, we identified 13 HLA alleles (9 HLA-I and 4 HLA-II) that occurred at greater frequency in very old individuals (age ≥90 years) as compared to younger individuals. Remarkably, for those 13 alleles, the predicted binding affinities were significantly higher for HERVK than for the other viruses (P < 0.001). ApoE genotypes did not differ significantly between older and younger groups.DiscussionTaken together, the results showed that HLA-HERVK binding affinity is a robust predictor of longevity and that HLA alleles that bind with high affinity to HERVK were enriched in very old individuals. The findings of the present study highlight the influence of interactions between host immunogenetics and virus exposure on longevity and suggest that specific HLA alleles may promote longevity via enhanced immune response to specific common viruses, notably HERVK.